Effect of Pilates on Sleep Quality: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Chen, Zehua; Ye, Xiangling; Shen, Zhen; Chen, Guoqian; Chen, Weijian; He, Ting; Xu, Xuemeng (Frontiers in Neurology, 2020)
Objective: Pilates exercise is increasingly used to improve sleep quality, but relevant evidence remains unclear. We aimed to estimate the effect of Pilates on sleep quality. Methods: Five databases were searched for articles published until 10 December 2019. Two investigators screened the articles and extracted data from each included study. A meta-analysis was performed to evaluate the effect of Pilates on sleep quality, assessed using the Pittsburgh Sleep Quality Index (PSQI). Results: Six randomized controlled trials (RCTs) comprising 477 participants were included according to the inclusion and exclusion criteria in the study. All included studies reported the positive effects Pilates had on sleep quality. The Pilates group (PG) significantly lowered the PSQI total score (MD = −3.60, 95%CI: [−5.41, −1.78), P = 0.0001, I2 = 97%) compared to the non-exercising control group (CG), whereas no significant improvement in use of sleep medication was observed (MD = −0.33, 95%CI: [−0.73, −0.06), P = 0.10, I2 = 68%). However, in a subgroup analysis, we found that there was no significant reduction in the PSQI total score for healthy participants over 40 years old (MD = −3.73, 95%CI: [−7.89, 0.42], P = 0.08, I2 = 98%) and for postmenopausal women (MD = −5.55, 95%CI: [−13.98, −2.89], P = 0.20, I2 = 98%). Conclusions: Overall, Pilates improved sleep quality but had no significant effect on the use of sleep medication. However, Pilates showed no significant impact on sleep quality for healthy individuals over 40 years old and for postmenopausal women. Well-designed and large-scale RCTs are needed in the future.